Wise Circe’s Cult of Nature - Orion, Loretta (Ethnologies, 1998)
During the Renaissance, the philosopher, Giordano Bruno promoted “a religion of love” and a “cult of nature” to replace the authoritarian Christian religions. The Inquisition had him burned at the stake for his heresy. Lori Bruno, who believes the martyred Bruno is her ancestor, is a priestess of stregheria, an Italian family tradition of nature worship and witchcraft. Relatives who taught her this religion also conveyed the belief that their ancestor Bruno was a witch. Lori had transformed this historical figure into a culture-hero by enhancing family lore with historical research and personal visions of Bruno. In this paper we learn how family lore becomes coven lore and how historical figures inspire religious practice when they acquire sacred status.